Information Linkages and Correlated Trading - Colla, Paolo; Mele, Antonio (Review of Financial Studies, 2010)
In a market with informationally connected traders, the dynamics of volume, price informativeness, price volatility, and liquidity are severely affected by the information linkages every trader experiences with his peers. We show that in the presence of information linkages among traders, volume and price informativeness increase. Moreover, we find that information linkages improve or damage market depth, and lower or boost the Traders' profits, according to whether these linkages convey positively or negatively correlated signals. Finally, our model predicts patterns of trade correlation consistent with those identified in the empirical literature: trades generated by “neighbor” traders are positively correlated and trades generated by “distant” traders are negatively correlated.